Dramatically enhanced polarization in (001), (101) and (111) BiFeO3 thin films due to epitaxial-induced transitions - Li, Jiefang (2011)
Dramatically enhanced polarization has been found for (001), (101), and (111) films, relative to that of BiFeO3 crystals. The easy axis of spontaneous polarization lies close to (111), for the various oriented films. BiFeO3 films grown on (111) have a rhombohedral structure, identical to that of single crystals; whereas films grown on (101) or (001) are monoclinically distorted from the rhombohedral structure, due to the epitaxial constraint.